Implementasi Metode Fuzzy Tsukamoto dalam Menangani Ketersediaan Barang - Randy Sugito Djie; Syaiful Rahman; Hasniati (STMIK KHARISMA Makassar, 2016)
This research aims to predict the amount of goods (aluminum casement type) which must be ordered to deal with the availability of goods in the PT. Happy Aluminium. For that aims, it is proposed to use fuzzy Tsukamoto method. Fuzzy Tsukamoto can be applied to predict the amount of goods and tolerate data that is both flexible and volatile. Data collection techniques in this research was conducted through interviews with sources and literature studies. Applications designed using Unified Modeling Language (UML), use case diagrams, class diagrams and activity diagrams. The design of the database using the Entity Relationship Diagram (ERD). Furthermore, the design is implemented using Visual Basic 6.0 programming language and uses MySQL database storage. Results of the research were able to make predictions about the amount of goods (aluminum casement type) to be ordered so it can handle the availability of goods.